Hubungan pola tidur dengan hipertensi pada lansia - Sari, Vera Evita; Salmiyati, Suri; Sudyasih, Tiwi (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: The increasing number of elderly people has led to a rise in the prevalence of degenerative diseases, one of which is hypertension, which remains a major health problem in the elderly. In addition to aging and physiological changes, lifestyle factors, such as sleep patterns, play a role in the development of hypertension, as older adults often experience changes in sleep duration and quality. Disturbed sleep patterns can increase sympathetic nervous system activity and stress hormones, leading to increased blood pressure. Purpose: To determine the relationship between sleep patterns and hypertension in elderly Posyandu elderly. Method: This research used a cross-sectional design. The population was 41. Purposive sampling was used, resulting in a sample size of 40 respondents. Data collection techniques included a digital sphygmomanometer and a questionnaire. The chi-square test was used for data analysis. Results: The results of the Chi-Square test showed a p-value of (0.001) < (0.05), meaning that statistically there was a significant relationship between sleep patterns and hypertension in respondents in this study. The majority of respondents experienced poor sleep quality with stage II hypertension of 19 respondents (47.5%). Conclusion: There is a link between sleep patterns and hypertension in the elderly, with poor sleep patterns contributing to increased blood pressure. Improving sleep patterns should be part of promotive and preventive efforts to control hypertension in the elderly at the community level.   Keywords: Elderly; Hypertension; Sleep Patterns.   Pendahuluan: Peningkatan jumlah lanjut usia (lansia) berdampak pada meningkatnya prevalensi penyakit degeneratif, salah satunya hipertensi yang masih menjadi masalah kesehatan utama pada kelompok usia lanjut. Selain faktor penuaan dan perubahan fisiologis, gaya hidup seperti pola tidur berperan dalam terjadinya hipertensi, mengingat lansia sering mengalami perubahan durasi dan kualitas tidur. Gangguan pola tidur dapat meningkatkan aktivitas sistem saraf simpatis dan hormon stres sehingga memicu peningkatan tekanan darah. Tujuan: Untuk mengetahui hubungan antara pola tidur dengan Hipertensi pada lansia posyandu lansia. Metode: Metode penelitian ini menggunakan rancangan cross-sectional. Populasi penelitian ini sebanyak 41. Teknik sampling menggunakan purposive sampling sehingga sampel yang digunakan sebanyak 40 responden. Teknik pengumpulannya menggunakan sphygmomanometer digital dan kuisioner. Metode analisa data nya menggunakan uji Chi-Square. Hasil: Uji Chi-Square menunjukkan nilai p-value (0.001) < (0.05), artinya secara statistik terdapat hubungan yang signifikan antara pola tidur dengan hipertensi pada responden dalam penelitian ini. Mayoritas responden mengalami kualitas tidur buruk dengan hipertensi stage ll sebanyak 19 responden (47.5%). Simpulan: Terdapat hubungan antara pola tidur dengan hipertensi pada lansia, di mana pola tidur yang buruk berkontribusi terhadap peningkatan tekanan darah. Perbaikan pola tidur perlu menjadi bagian dari upaya promotif dan preventif dalam pengendalian hipertensi pada lansia di tingkat komunitas.   Kata Kunci: Hipertensi; Lansia; Pola Tidur.